2015
DOI: 10.5539/ass.v11n28p65
|View full text |Cite
|
Sign up to set email alerts
|

Self-Efficacy: As Moderator of the relation between Family Factors and Adolescent Cigarette Smoking Behavior

Abstract: In this study, the relationship between family factors (family cohesion and family adaptability) and cigarette smoking behaviour was investigated. The other objective of this research was exploring the moderating impact of self-efficacy on the link of family cohesion and family adaptability with cigarette smoking behaviour among Iranian youngsters in the city of Kerman. Following cluster sampling method, the data was collected from current cigarette smoking adolescents (n = 300) from 22 high schools across Ker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Likewise, a study by Ehret, Ghaidarov and LaBrie 46 revealed that the likelihood of developing alcohol dependency was greater in those with lower self-efficacy when it came to refusing alcohol. Golestan and Abdullah 47 also found that adolescent smoking risk characteristics are influenced by self-efficacy. In the light of that, we present the third hypothesis:…”
Section: Introductionmentioning
confidence: 95%
“…Likewise, a study by Ehret, Ghaidarov and LaBrie 46 revealed that the likelihood of developing alcohol dependency was greater in those with lower self-efficacy when it came to refusing alcohol. Golestan and Abdullah 47 also found that adolescent smoking risk characteristics are influenced by self-efficacy. In the light of that, we present the third hypothesis:…”
Section: Introductionmentioning
confidence: 95%
“…Empirical studies have supported this hypothesis. For instance, Golestan and Abdullah 40 found that the existence of a significant moderating function of self-efficacy regarding the effect of environmental risk factors on cigarette smoking behavior amongst youngsters. Likewise, Jang et al 41 found that drinking refusal self-efficacy moderated the relationship between descriptive norms and adolescent drinking behavior, such that participants with higher refusal self-efficacy were less likely to be affected by descriptive norms.…”
Section: Introductionmentioning
confidence: 99%
“…According to Golestan et al [109], around the world, cigarette smoking is not considered as dangerous as narcotic drugs, since there is no country in which adolescents do not smoke. However, cigarette smoking among adolescents is considered a global and complex public health problem as it affects the development of a person's physical, emotional, spiritual, and social well-being.…”
Section: Smokingmentioning
confidence: 99%